Is begging a Roma cultural practice? Answers from the Italian legal system and anthropology. Issue 1 (June 2016) - RUGGIU, ILENIA
Abstract : Several Italian judges, including the members of the Supreme Court, have defined begging with children as a "Roma cultural practice". In response, the Italian Parliament enacted law no. 94/2009, which severely represses the practice. The article contests that begging is a Roma cultural practice and claims, instead, that it is an economic practice which may sometimes connect to other elements of Roma culture. The article critiques both the cultural argument put forward by Italian judges, and Italian law no. 94/2009, neither of which serves to defend the rights of Roma children. It concludes by suggesting a different kind of legal approach to child begging, more respectful of the constitutional duty of solidarity and protection of the family, and based on social policies rather then criminal repression.